ANALISIS FAKTOR PENYEBAB UTAMA KERUSAKAN BERKAS REKAM MEDIS PADA RUANG FILING DI RSUP Dr. SOERADJI TIRTONEGORO KLATEN - Rifka Faizatus Tsaniyah; Amelia Herdianti P; Shinta Pridani P; Afin Maulana Y; Rifaldi Firdausi MF; Feby Erawantini; Gandu Eko Julianto Suyoso; Yuliana Dwi Utami (Politeknik Negeri Jember, 2022)
Hospital is a complete individual health service institution including promotive, preventive, curative and rehabilitative that provides inpatient, outpatient and emergency services with the aim of improving the quality of service and maintaining hospital standards. The results of a preliminary study conducted at RSUP dr. Soeradji Tirtonegoro is known that there are medical record documents that have been damaged. This study aims to analyze the main factors causing damage to medical record files in the filing room at dr. Soeradji Tirtonegoro Klaten. This type of research uses qualitative and data collection uses observation, interviews using elemental analysis of 5M management (Man, Material, Method, Machine, Money), while determining problem priorities using the USG method (Urgency, Seriousness, Growth) and problem solving using techniques brainstorm. Subjects in this study were medical record officers in the filing room as many as 7 people. The results obtained are that there is a lack of medical record officers in the filing room, the roll o'pack is full, there is no training in activities in the filing department, the filing officer lacks discipline, there is no SPO related to the protection and maintenance of medical records from damage. By using the USG method and brainstorming techniques, it can be seen that the main cause of damage to medical record files and the agreed solution is related to the lack of human resources in the filing room, the score obtained is 89. Suggestions made by researchers are the addition of officers in the room. filing using the method of calculating ABK Cases, adding file storage racks, the existence of SOP for protection and maintenance of medical records from damage